Enhancement of the yield of high-quality ingots in the zone-melting growth of p-type bismuth telluride alloys - Ha, HP; Hyun, DB; Byun, JY; Oh, YJ; Yoon, EP (KLUWER ACADEMIC PUBL, 2002)
The influences of zone melting growth speed on the thermoelectric properties of p-type bismuth telluride alloys were investigated. When the growth speed was fast, thermoelectric properties were uniform along ingots, as the composition of the molten zone did not change significantly. On the other hand, when growth speed was slow, thermoelectric properties varied along ingots due to the change of the solidified composition determined by the composition of a molten zone. The maximum figure of merit appeared in the middle of an ingot grown at slow growth speed. In the present study, the molten zone leveling method was developed as an attempt to extend the region with high figure of merit. The basic idea of the method was to preserve a uniform composition of liquid at the solid-liquid interface during growth of an ingot so as to obtain a uniform composition of precipitated solids. Ingots composed of two sections with different compositions were used to control the accumulation of Te within the molten zone. As a result, high figure of merit could be obtained over more than 90% of ingot when zone melting growth speed was slow. (C) 2002 Kluwer Academic Publishers.